Production Optimization Using Fuzzy Linear programming Method (Case Study: UMKM Untir-untir and Raja Manis Factory) - Nababan, Esther S.M.; Sihaloho, Agnes; Husna, Khatimatul; Ilham, Rafida (Journal of Research in Mathematics Trends and Technology, 2022)
Production efficiency and performance optimization in a company can be achieved by using an optimization model. An optimisation model can be written in a function of equation and equation known as a Linear Program. A Linear program can be combined with a fuzzy value to adjust a production problem model that is heavily dependent on an unstable supply. This modeling is known as Fuzzy Linear programming. Using Fuzzy Linear programming, the production problems of micro, small and medium-sized enterprises Untir-untir and King Sweet are analyzed and solved with the heLP of simulation programs. Fuzzy Linear programming solutions use simplex methods using POM-QM software to complete complex calculations. Completion with the fuzzy simplex method consists of several steps namely calculating the optimal bottom and upper boundaries with the maximizing simplex technique, modifying the initial equation by adding the variable Î», and finishing it with the two-phase simplex approach. Results of completion with the simulation program showed the estimated amount of profit using the Linear Program equation of Rp. 1,378,723 and using the Fuzzy Linear programming equation with a 10% tolerance of Rp. 1,447,470.